2017
DOI: 10.1039/c7nr00703e
|View full text |Cite
|
Sign up to set email alerts
|

Topological landscapes of porous organic cages

Abstract: We define a nomenclature for the classification of porous organic cage molecules, enumerating the 20 most probable topologies, 12 of which have been synthetically realised to date. We then discuss the computational challenges encountered when trying to predict the most likely topological outcomes from dynamic covalent chemistry (DCC) reactions of organic building blocks. This allows us to explore the extent to which comparing the internal energies of possible reaction outcomes is successful in predicting the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
206
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(209 citation statements)
references
References 82 publications
1
206
0
2
Order By: Relevance
“…To efficiently synthesize shape‐persistent organic cages in high yields, dynamic covalent chemistry (DCC) turned out to be the synthetic method of choice . Cages of various sizes and geometries should be accessible by choosing the right precursors . And indeed a large number of geometries and topologies have been realized till date including prisms, tetrahedra, cubes, cuboctahedra, octahedra, tetrapods and others…”
Section: Methodsmentioning
confidence: 99%
“…To efficiently synthesize shape‐persistent organic cages in high yields, dynamic covalent chemistry (DCC) turned out to be the synthetic method of choice . Cages of various sizes and geometries should be accessible by choosing the right precursors . And indeed a large number of geometries and topologies have been realized till date including prisms, tetrahedra, cubes, cuboctahedra, octahedra, tetrapods and others…”
Section: Methodsmentioning
confidence: 99%
“…Previously, a range of Tri 2 Di 3 species have been reported that are formed using an imine condensation strategy—these cage molecules consist of two tri‐topic and three di‐topic building blocks . Following this, we reported a high‐throughput workflow that used a robust synthetic method for organic cage discovery, that also included a number of Tri 2 Di 3 species . While our modelling suggested that organic cages of this topology tend to have cavities that are too small to host gaseous guests based on their kinetic diameters, meaning their porosity is not typically studied, the reduced versions of these small capsular cages, or cryptands/cyclophanes, have been previously studied as binding receptors .…”
Section: Resultsmentioning
confidence: 81%
“…Our aim was to use a multi‐component imine condensation to access a socially self‐sorted and controlled assembly incorporating more than one cage, instead of self‐sorted binary cages. We therefore decided to investigate the one‐pot multi‐component reaction of a tri‐topic amine and di‐topic aldehyde (as used in the formation of B1 , a Tri 2 Di 3 cage), along with a tetra‐topic aldehyde that has the same 1,3‐dialdehyde substitution pattern (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Santolini et al klassifizierten kürzlich die 20 wahrscheinlichsten Käfigtopologien fürd i-, tri-und tetratopische Vorstufen, [130] von denen zwçlf bereits präparativ realisiert wurden. Santolini et al klassifizierten kürzlich die 20 wahrscheinlichsten Käfigtopologien fürd i-, tri-und tetratopische Vorstufen, [130] von denen zwçlf bereits präparativ realisiert wurden.…”
Section: Organische Bausteineunclassified